PENGARUH TERAPI MUSIK TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF DI KLINIK KELUARGA PISANGAN BARU KELURAHAN PISANGAN BARU KECAMATAN MATRAMAN JAKARTA TIMUR TAHUN 2016 - Triana Indrayani; Nuricha Arselina (Jurnal Ilmu dan Budaya, 2018)
Labor pain is a physiological condition. The pain is caused by uterine contractions and cervical dilation. The longer the pain, the strongerit will be, while the peak of pain occurs in the active phase. This study aims to determine the effect of music therapy on active phase of first stage labor pain at Klinik Keluarga Pisangan Baru, Pisangan Baru Village,MatramanDistrict in 2016. The study used quasi-experiment with pretest-posttest only design with control group. The population in this study is in the whole mother maternity normal at Klinik Keluarga Pisangan Baru its amount is 24 people. While the sampling method used "total sampling". The number of sample were 24 women (12 in experimental group and 12 in control group). The pain was measured by FLACC (Faces, Legs, Activity, Cry, and Consolability) scale. The statistical test used was Wilcoxon Signed Rank Test.The result of the studyindicatedthat there is an effect of music therapy on active phase of first stage labor pain with the result of (p-value 0.019 <α 0.05). Based on the conclusion,it is suggested that music therapy can be used as an interventionto reduce the intensity of labor pain in childbirth.